Endomyocardial biopsy diagnosis of acute cardiac allograft rejection - Hunt, James Barrie (Division of Anatomical Pathology, 2017)
The aims of the present investigation are fourfold: (i) to review the range of non-invasive methods that may be used to diagnose acute cardiac allograft rejection; (ii) to review the use of the bioptome in sampling the donor heart endomyocardium; (iii) to review the light microscopic and histological grading of acute cardiac rejection; (iv) to characterise the mononuclear populations in endomyocardial biopsy samples and correlate the findings with the light microscopic appearances of the same biopsy specimens.